Performance of Eucalyptus Species in Nainital Tarai of Uttar Pradesh - Chandra, J. P.; Yadava, M. P. S.; Gandhi, J. N. (Indian Forester, 1998)
Performance trial of 25 provenances of six species of eucalypts was conducted at R&D Station of M/s WIMCO Seedlings Limited located at Rudrapur, Nainital District in U.P. Out of 25 provenances tried, 10 were of E. camaldulensis, 5 were of E. grandis, 4 were of E. saligna, 3 were of E. brassiana, 2 were of E. urophylla and 1 was of Mysore gum. Observations of height, DBH, basal area, volume/ha were recorded. It was observed that provenance 13022 NW of Caboolture, 12970 SFR 194 Herberton Range, Qld. of E. grandis and 13026 South of Calliope, Qld. of E. saligna yielded higher wood per unit area than rest of the provenances under study and were significantly better that control i.e. Mysore gum CBJ-38. Provenance 13395 of E. brassiana yielded poorest.